Oxygen-dependent proton efflux in cyanobacteria (blue-green algae). - Scherer, S (1984)
The oxygen-dependent proton efflux (in the dark) of intact cells of Anabaena variabilis and four other cyanobacteria (blue-green algae) was investigated. In contrast to bacteria and isolated mitochondria, an H+/e ratio (= protons translocated per electron transported) of only 0.23 to 0.35 and a P/e ratio of 0.8 to 1.5 were observed, indicative of respiratory electron transport being localized essentially on the thylakoids, not on the cytoplasmic membrane. Oxygen-induced acidification of the medium was sensitive to cyanide and the uncoupler carbonyl cyanide m-chlorophenylhydrazone. Inhibitors such as 2,6-dinitrophenol and vanadate exhibited a significant decrease in the H+/e ratio. After the oxygen pulse, electron transport started immediately, but proton efflux lagged 40 to 60 s behind, a period also needed before maximum ATP pool levels were attained. We suggest that proton efflux in A. variabilis is due to a proton-translocating ATP hydrolase (ATP-consuming ATPase) rather than to respiratory electron transport located on the cytoplasmic membrane.